A note on the spatial and temporal distribution of humpback whales (Megaptera novaeangliae) off Venezuela, Southeastern Caribbean - Acevedo, R.; Oviedo, L.; Silva, N.; Bermudez-Villapol, L. (J. Cetacean Res. Manage., 2023)
This paper presents information on the spatial and temporal distribution of humpback whales in Venezuelan waters. Using a relational database containing information from the museums of Venezuela, published and unpublished records were incorporated into a Geographical Information System (MapInfo Professional 7.0). A total of 53 records were gathered, of which sightings made up 72%, followed by acoustic sampling (9%) intentional capture (6%), stranding (6%) and unknown records (8%). Humpback whales were mainly sighted over the continental shelf of the northeastern region in shallow waters of 0-100m in depth. The date on which each record was made supports the seasonal occurrence of North Atlantic humpback whales off the Venezuelan coast. Opportunistic sightings and stranding records from the austral winter months do not give conclusive proof that Southern Hemisphere humpback whales are present during this time, but lead to the hypothesis that whales migrate from Brazil. Systematic research effort (especially photo-identification) is recommended in order to better understand humpback whale movements, distribution and identity.